Prof. Neville Hacker: honesty, empathy, collegiality and dedication - Zhou, Silvia (Gynecology and Pelvic Medicine; Vol 2 (October 2019): Gynecology and Pelvic Medicine, 2019)
In about 1984, under the leadership of Dr. J. George Moore, 50–60 experts from the main UCLA campus, Cedars Sinai Medical Center, Harbor (LA County) General Hospital, Martin Luther King Jr Memorial Hospital and Kern County Medical Center, commenced to write the book Hacker & Moore’s Essentials of Obstetrics and Gynecology. At the same time, Prof. Neville F. Hacker was invited by Dr. Moore to edit the book. In the past three decades, Prof. Neville F. Hacker has persistently devoted his efforts to this book series as an editor.